The Utilization of Fermented Rice Straw Ammoniation Feed (Amofer ) to Increase Body weight Gain of Bali bull in Batu Kuta Lombok Barat - Abyadul Fitriyah; Ria Harmayani; Aisah Jamili; Yuni Mariani; Ni Made Andry Kartika; Nefi Andriana Fajri; Isyaturriyadhah Isyaturriyadhah (Baselang, 2022)
The utilization of rice straw waste as fermented ammonia (Amofer) for cattle farming was done in Desa Batu Kuta Kecamatan Narmada Kabupaten Lombok Barat from April-September 2021 with aims to introduce Amofer feed technology to increase body weight of bulls. The research procedures that have been carried out includes: 1). Amofer feed manufacture by adding ammonia in rice straw (Ammonia Straw), and 2). Amofer feeding management. This study was used 15 Bali bulls with 225 kg – 250 kg of body weights. There are three (3) treatments of Amofer feeding management, namely: R0 = Farmer's treatment (straw+concentrate); R1 = Forage 30% (15% elephant grass + 15% gamal grass) + 69 % Amofer feed + 1 % Concentrate (corn + bran); R2 = Forage 70% (35% elephant grass + 35% gamal grass) + 29 % Amofer feed + 1 % Concentrate (corn + bran). Parameters measured were feed consumption (FC) and daily body weight gain (DBWG). The results showed that the highest of FC was found on Bali bull with R-2 treatment (14.42 kg/each/day), and the highest of DBWG was shown by Bali bull whith R-2 treatment (0.66 kg/each/day). It is concluded, the Amofer feed formula in R2 treatment was more efficiently applied to ruminants with the aim of fattening cattle.